2015
DOI: 10.3109/09513590.2015.1018166
|View full text |Cite
|
Sign up to set email alerts
|

The role of TGFβsuperfamily members in the pathophysiology of endometriosis

Abstract: The transforming growth factor-beta (TGFβ) superfamily comprises over 30 dimeric proteins with conserved structures, which play important roles in the control of cellular proliferation, differentiation and apoptosis. These proteins are expressed and finely regulated in human endometrium during the menstrual cycle, which is consistent with their effects on endometrial cell proliferation and tissue remodeling. This review is focused on summarizing the role of key members of the TGFβ superfamily in the pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…The expression of these integrins is tightly regulated by diverse molecules, such as interleukin (IL)-1, IL-8, macrophage inhibitory factor (MiR)-183, prostaglandin E2, and a cannabinoid receptor agonist ( 7 , 9 11 , 37 , 38 ). However, despite the obvious importance of TGF-β1 in the progression of endometriosis ( 13 , 17 ), there have been no reports of the TGF-β1 function in the regulation of integrins in endometrial cells. Thus, we examined the regulation of integrins by TGF-β1 and their role in the initiation of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of these integrins is tightly regulated by diverse molecules, such as interleukin (IL)-1, IL-8, macrophage inhibitory factor (MiR)-183, prostaglandin E2, and a cannabinoid receptor agonist ( 7 , 9 11 , 37 , 38 ). However, despite the obvious importance of TGF-β1 in the progression of endometriosis ( 13 , 17 ), there have been no reports of the TGF-β1 function in the regulation of integrins in endometrial cells. Thus, we examined the regulation of integrins by TGF-β1 and their role in the initiation of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…In human endometriosis lesions, TGF-β1 expression has been found in macrophages, endometrial epithelial cells, endometrial stromal cells, and mesothelial cells ( 13 , 24 ). Elevated levels of secreted TGF-β1 in peritoneal fluid influenced many steps in the progression of endometriosis, including immune surveillance, cell adhesion and invasion into the peritoneum, angiogenesis, and growth of implants ( 13 , 17 ). The response of TGF-β1 measured by endometrial-mesothelial adhesion is different between normal endometrial HES cells and ectopic endometrial cells (12Z).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased secretion of inflammatory cytokines [7], chemokines [93], and growth factors [94, 95] in endometriosis has been widely demonstrated. Although the presence of endometriotic pain is mostly associated with the disease progression [96], the generation of the pain in endometriosis remains unknown.…”
Section: Macrophage and Nerve Interaction In Endometriosismentioning
confidence: 99%
“…We found that the NF‐κBp50 inhibitor, SN50, decreased the expression of CD36 and SIRP‐α in macrophages that were treated with normal but not eutopic endometrial homogenate, suggesting the involvement of different macrophage regulatory mechanisms between normal and eutopic endometrium. Previous evidence has demonstrated increased levels of TGF‐β in eutopic and ectopic endometrial lesions, accompanied by decreased immune cell activity within the peritoneum, further fuelling EM lesion development . Han et al reported that TGF‐β1/2 significantly decreases the expression of CD36 in macrophages through a mechanism that involves phosphorylation of mitogen‐activated protein kinase .…”
Section: Discussionmentioning
confidence: 99%